Avaliação do efeito do exercício físico no metabolismo de ratas diabéticas prenhes - Volpato, Gustavo Tadeu [UNESP]; Damasceno, Débora Cristina [UNESP]; De Campos, Kleber Eduardo [UNESP]; Rocha, Renato; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (My University, 2006)
The aim of the present study was to evaluate if physical exercise (swimming program), begun in different periods of pregnancy of diabetic rats, promotes changes in the maternal metabolism. Severe diabetes was induced in female rats using Streptozotocin. The rats were mated and randomly assigned to three groups (n = 13 rats/group): sedentary (G1) or exercised from day zero (G2) or day seven (G3) to day 21 of pregnancy. The exercise consisted of a moderate swimming program. During pregnancy, the body weight and glycemic level were weekly evaluated. All the female rats were killed on day 21 of pregnancy to carry out laparotomy. The blood samples were collected to determine total protein, triglycerides, total cholesterol and VLDL-cholesterol. Liver and muscle samples were collected to determine hepatic and muscular glycogen, respectively. Regardless the initial moment, the exercise did not alter glycemic level, body weight evolution and total protein, hepatic and muscular glycogen concentrations. However, the swimming program begun on the 7th day of the pregnancy decreased the triglyceride rate (G1 = 369.10 ± 31.91 mg/dL; G2 = 343.32 ± 162.12 mg/dL; G3 = 212.35 ± 70.32 mg/dL), total (G1 = 176.48 ± 28.25 mg/dL; G2 = 141.33 ± 19.77 mg/dL; G3 = 129.86 ± 33.16 mg/dL), and VLDL (G1 = 64.92 ± 24.41 mg/dL; G2 = 63.54 ± 28.31 mg/dL; G3 = 42.53 ± 14.12 mg/dL) cholesterol concentrations compared to G1 group. Physical exercise did not interfere on the maternal glycemic levels. Thus, the swimming program began on the day seven of the pregnancy was a beneficial treatment for the lipidic profile of the diabetic rats. This result validates an association of regular physical activity to diet and insulin treatment in pregnancy complicated by diabetes.
Evaluation of the effect of physical exercise in the metabolism of pregnant diabetic rats
Keywords: Diabetes mellitus; Exercise; Metabolism; Pregnancy; Rats